Elastomer-Based Sealing O-Rings and Their Compatibility with Methanol, Ethanol, and Hydrotreated Vegetable Oil for Fueling Internal Combustion Engines - Müller, Miroslav; Mishra, Rajesh Kumar; Šleger, Vladimir; Pexa, Martin; Čedík, Jakub (Materials (Basel, Switzerland), 2024)
Green methanol, ethanol, and diesel-based hydrotreated vegetable oils are some of the renewable liquid fuels that show satisfactory performance in diesel engines. A notable advantage of these fuels is that they are renewable and do not require significant modifications in the existing engines for successful operation. Suitable fuel systems, especially their material compatibility, remain unresolved, and therefore, it is a weak link in their large-scale adaptation. Elastomer-based sealing O-rings lose their mechanical properties after a short exposure time to these fuels, adversely impacting their functionality. This research study evaluated the long-term material compatibility of different elastomer-based sealing materials by immersing the O-rings in these test fuels (hydrotreated vegetable oil, methanol, ethanol, and diesel) for different time intervals (i.e., up to 15 months). The material compatibility was assessed mainly by investigating these changes in various mechanical properties of these O-rings, namely tensile strength (ΔTs), elongation at break (ΔEb), Shore A hardness (ΔH), and mass (ΔM). The degradation of mechanical properties was studied and analyzed during the immersion interval from 0.9 to 15.2 months and compared with O-rings kept in a normal atmosphere. It was noted that individual fuels affect various mechanical properties significantly. In a short interval of 0.9 months (28 days), significant changes in the mechanical properties of the sealing O-rings were observed.
Keywords: tensile strength; methanol; material compatibility; green diesel; ethanol; O-rings